Testing the influence of isolation and adaptive evolution on genetic and phenotypic differentiation in a neotropical montane bird (2010)
Population differentiation is promoted by geographic isolation produced by the emergence of ecological or geographic barriers, isolation by distance, and by adaptation to different environments. Owing to its topographic complexity, the Andes are an ideal setting to study the role of these forces on species differentiation. In this study, we evaluate the influence of these mechanisms on the differentiation among populations of a nectarivorous Andean bird, the White-side Flower piercer (Diglossa albilatera) using data on genetic morphological, environmental connectivity, and ecological variation. Phylogenetic and population genetic analyses showed that D. albilatera includes two clades separated by geographic barriers across which gene flow is restricted. However, such barriers were not clearly associated with morphological differentiation. Analyses based on ecological connectivity revealed no association between genetic and morphological variation and ecological barriers. One of the clades, but not the other, showed evidence isolation-by-distance in genetic data, but there was no relationship between geographic distance and morphological distances. Finally, we found a significant correlation morphological and ecological variation, which supports the hypothesis of natural selection. In sum, our data reveal genetic (but not morphological) differentiation associated with geographic barriers at large scale, but not with ecological barriers at finer scales. In addition, we found partial support for isolation by distance and for natural selection as drivers of genetic and morphological differentiation, respectively.